NURSING MOTHERS SATISFACTION AT PUSKESMAS AMPENAN WORKING AREA - Rani Sulistiawati; Tiyas Kusumaningrum; Retnayu Pradanie (Universitas Airlangga, 2022)
Introduction: When moms who could only extract a few milks in advance or not at all were given the Marmet method, the results were excellent. One of the safest methods for encouraging breast milk to create more breast milk is Marmet's method. Methods: A cross-sectional study was conducted in this case. This research seeks to ascertain how Marmet's approach affects nursing mothers' satisfy. 80 respondents were selected as research samples using cluster sampling. Mann Whitney and Wilcoxon's Test, with a significant level of 0,05, were used to examine the data. Results: The Marmet technique has a significant impact on how satisfied mothers are with their ability to breastfeed, according to the statistical test results of the Wilcoxon Signed Rank Test in the treatment group with the value of sig (2-tailed) obtained p = 0.000 in which p 0.05 is considered significant. However, the control group received a p value of 0.083, which means that the Marmet approach had no significant impact on the mothers' satisfaction with breastfeeding. Conclusion: After using the Marmet approach to intervene, the mother is now more satisfied with her breastfeeding